Bivariate Generalization of The Inverted Hypergeometric Function Type I Distribution (2012)
The bivariate inverted hypergeometric function type I distribution is defined by the probability density function proportional to x ν1−1 1 x ν2−1 2 1 + x1 + x2 −(ν1+ν2+γ) 2 F1 (α,β;γ;(1 + x1 + x2 )−1),x1 > 0, x2 > 0, where ν1, ν2, α, β and γ are suitable constants. In this article, we study severalproperties of this distribution and derive density functions of X1/X2, X1/(X1 + X2) and X1 + X2. We also consider several products involving bivariate inverted hypergeometric function type I, beta type I, beta type II, beta type III, Kummer-beta and hypergeometric function type I variable